2012
DOI: 10.2478/10004-1254-63-2012-2224
|View full text |Cite
|
Sign up to set email alerts
|

Chronic effects of environmental biomass smoke on lung histopathology in turkish non-smoking women: a case series

Abstract: Biomass is widely used for fuel in developing countries. Particles and gases of biomass burning may cause changes in the lung. In this prospective study we investigated histopathological changes in the lungs of 42 non-smoking women [mean age (59±10) years] caused by biomass smoke. We valuated exposure to biomass smoke, case histories, and the fi ndings of physical examination, radiology, bronchoscopy, and lung histopathology. Mean exposure to biomass smoke was (28±9) hour-year (1 hour-year equals 365 hours of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
(23 reference statements)
0
3
0
2
Order By: Relevance
“…5 In a study conducted in Turkey, it was reported that exposure to biomass may cause lung cancer as well as various lung diseases. 6 Pregnancy-associated lung cancer is defined as lung cancer detected during pregnancy and within 1 year after birth. In a retrospective analysis by Yang Lei et al, 2 including clinical manifestations, treatments, and outcomes, the median age of 77 pregnancy-related lung cancer cases reported up to 2021 was 34.…”
Section: Discussionmentioning
confidence: 99%
“…5 In a study conducted in Turkey, it was reported that exposure to biomass may cause lung cancer as well as various lung diseases. 6 Pregnancy-associated lung cancer is defined as lung cancer detected during pregnancy and within 1 year after birth. In a retrospective analysis by Yang Lei et al, 2 including clinical manifestations, treatments, and outcomes, the median age of 77 pregnancy-related lung cancer cases reported up to 2021 was 34.…”
Section: Discussionmentioning
confidence: 99%
“…The inhaled particles of biomass fuel were accumulated at the branching portion of bronchus, while some were taken up by macrophages or bronchial epithelial cells . Anthracotic carbonaceous pigments can deposit in the bronchi subepithelium and interalveolar septa, increase airway inflammation, and might cause fibrosis or hypertrophy of the bronchial wall and luminal narrowing, ultimately resulting in BAF. There's no evidence that biofuel smoke can cause FM directly, but biofuel‐associated BAF is frequently coexisting with TB (33.9%) and mediastinal lymphadenopathy (66.0%), so that biofuel‐associated BAF might be indirectly correlated with FM.…”
Section: Discussionmentioning
confidence: 99%
“…We then read the full text of the remaining 117 studies. Studies that were impossible to distinguish female ETS exposure [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], studies without risk of ETS [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], studies that were published more than once, studies with a subset of cases [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , …”
Section: Methodsmentioning
confidence: 99%